2017
DOI: 10.1016/j.chempr.2017.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-Based Receptors Mimic Protein-Ligand Recognition

Abstract: SummaryThe self-assembly of a monolayer of ligands on the surface of noble-metal nanoparticles dictates the fundamental nanoparticle's behavior and its functionality. In this combined computational-experimental study, we analyze the structure, organization, and dynamics of functionalized coating thiols in monolayer-protected gold nanoparticles (AuNPs). We explain how functionalized coating thiols self-organize through a delicate and somehow counterintuitive balance of interactions within the monolayer itself a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
93
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 75 publications
(95 citation statements)
references
References 53 publications
2
93
0
Order By: Relevance
“…That is, positive cooperative interactions between peptide residues increase from surface distal to surface proximal regions. We attribute this to the increasing density and steric constraint of the surface proximal regions of the peptide chains that facilitate beneficial peptide‐peptide interactions, compared to the more flexible, solvent exposed surface distal region …”
Section: Figurementioning
confidence: 99%
“…That is, positive cooperative interactions between peptide residues increase from surface distal to surface proximal regions. We attribute this to the increasing density and steric constraint of the surface proximal regions of the peptide chains that facilitate beneficial peptide‐peptide interactions, compared to the more flexible, solvent exposed surface distal region …”
Section: Figurementioning
confidence: 99%
“…DLS and DOSY‐NMR experiments confirmed the absence of relevant aggregation. The affinity of the nanoparticles for salicylate was investigated by 1 H NOE‐pumping spectroscopy ,,. This experiment employs a diffusion filter to retain only the magnetization stemming from the nanoparticle spins, which is subsequently transferred via NOE only to those molecules in long‐lived interaction with the nanoparticle surface.…”
Section: Figurementioning
confidence: 87%
“…Later on, by studying the same nanoparticles using magnetization‐transfer NMR protocols, our group showed that they recognize and detect salicylate in water with a remarkable selectivity across highly similar isomers . Subsequent molecular‐dynamics (MD) simulations revealed that the host recognition is related to the spontaneous formation of deep pockets in the monolayer (Figure B) . The shape complementarity of these cavities with the guest structure explained the experimentally measured selectivity (salicylate vs. 4‐hydroxy‐benzoate).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations